Nursing students' readiness towards the 'new normal' in clinical practice: a distributed cognition qualitative perspective - Wei How Darryl Ang; Khairul Dzakirin Bin Rusli; Ying Lau; Siew Tiang Lau; Han Shi Jocelyn Chew (BMC, 2024)
Abstract Background Clinical practicums are a core component of baccalaureate nursing education. Following the coronavirus pandemic, there have been extensive changes in the workforce environment that may potentially affect nursing students' experience and readiness for clinical practicums. Methods A qualitative study was conducted to explore final-year nursing students' experiences and readiness for their final clinical practicum before becoming a registered nurse. A purposive sample of 24 final-year baccalaureate nursing students was included in this study. Individual semi-structured interviews were conducted face-to-face via Zoom. The data was analysed using an inductive thematic analysis approach. Results Three themes depicting students' experiences and clinical readiness were elucidated. The themes included: (1) Experiencing multiple concerns, (2) requiring a network of support, and (3) easing the transition to professional practice. Students considered the final clinical practicum as challenging and demanding which evoked numerous concerns. Conclusions Considering the stress that final-year nursing students experience, it will be important to devise strategies ranging from personal, relational, and environmental protective factors to enable their successful transition and completion of clinical practice.